Examining Transparency and Efficiency in Local Government Unit Disbursement Using Publicly Available Data from Cebu Province, Philippines - Salvador, Michel A.; Narsico, Peter G.; Estudillo, Joel L.; Delantar, Jinky R.; Narsico, Lalaine O. (Future Science / FSH-PH Publications, 2025)
This study examines the relationship between fiscal transparency and disbursement efficiency in a local government unit (LGU) in Cebu, Philippines, using publicly available 2024 fiscal data. Transparency is defined as the percentage of actual quarterly disbursement relative to the expected amount—25% of the annual budget per quarter—while efficiency measures the proportion of funds utilized. Both variables are derived from disbursement percentages, contributing to the strong positive correlation and unusually high regression coefficients observed. Linear regression analyses across four quarters reveal a consistent, statistically significant positive relationship between transparency and efficiency. Unstandardized coefficients (B) rise from 0.25 in Quarter 1 to 0.57 in Quarter 4, with Quarter 4 showing the highest standardized beta (β = 10.19, R² = 0.985). These results indicate that transparency increasingly influences efficiency as fiscal pressures mount toward year-end. The findings affirm transparency as a critical governance tool that aligns planned and actual disbursements to improve budget execution. Practically, enhanced transparency fosters accountability, strengthens fiscal discipline, and supports evidence-based resource allocation, which are vital for effective LGU policy and responsive public service delivery. However, the close operational linkage between transparency and efficiency warrants cautious interpretation of coefficient magnitudes. The study recommends performance-informed budgeting, improved monitoring, and inter-agency coordination to balance transparency with execution flexibility, optimizing resource use and governance outcomes in decentralized fiscal systems.